Shaheen Bagh: Muslim women contesting and theorizing citizenship and belonging during COVID-19 - Kapoor, Priya (Frontiers in Communication, 2022)
This paper documents an important slice of global South COVID-19 history, of primarily Muslim women’s protests against the Indian Government and Legislature for taking away their constitutional rights as citizens. The Shaheen Bagh mobilization has already become an important disruption in contemporary Indian history stirring public intellectuals to probe the question: ‘who is a citizen of India?’ in their scholarship and public-community work. By virtue of the disruption the event has caused in the enactment of the citizenship law, including other biometric directives, CAA-NRC-NPR, it has ceased to be regarded a minority or marginalized occurrence. This paper examines the writings of 4 prominent academics, public scholars, and thinkers (Romila Thapar, N. Ram, Gautam Bhatia, Gautam Patel) examining citizenship in contemporary India. In order to juxtapose and contrast expert musings on citizenship with embodied voices from the protest ground, I am critically reading two volumes with multiple essays, one edited (Seema Mustafa) and the other co-written by civically-engaged journalists (Ziya Us Salam and Uzma Ausaf) and members of the Shaheen Bagh protests. As an Indian-non-Muslim, I understand scholarship regarding Shaheen Bagh as an essential part of contemporary history, insofar as secularism is a worthy intercultural political philosophy to uphold at this temporal juncture of hate, intolerance and minority-baiting globally.